A novel synthetic approach to tyrosine dimers based on pterin photosensitization. (December 2017) - Reid, Lara O.; Castaño, Carolina; Dántola, M. Laura; Lhiaubet-Vallet, Virginie; Miranda, Miguel A.; Luisa Marin, M.; Thomas, Andrés H.
Abstract: Oxidative damage to proteins leads to a variety of modifications that are markers of pathogenesis. One of the most important modifications is the dityrosine (Tyr2 ) cross-link, resulting from an oxidative covalent bond between two tyrosines (Tyr). An optimized methodology for preparation of pure Tyr2 is important to investigate in detail its physicochemical properties and reactivity. Pterin (Ptr), the parent and unsubstituted compound of oxidized pterins, is able to photosensitize the cross-linking of free tyrosine (Tyr) and tyrosine residues of peptides and proteins through a photoinduced electron transfer mechanism. We have optimized a simple, one-step photocatalyzed formation of Tyr2, using Ptr as photocatalyst. Our procedure is carried out in aqueous solutions under UV-A radiation for few minutes. The purification of Tyr2 is performed by reverse-phase chromatography. The obtained highly pure solution is used to fully characterize the Tyr2 (exact mass and 1 H, 1 H- 1 H COSY; DEPT; HSQC and HMBC NMR experiments) and to deeper study its fluorescence properties. Highlights: Pterin photosensitizes the cross-linking of tyrosine through a type I mechanism. One-step pterin-photocatalyzed formation of tyrosine dimers has been optimized. Pterins might contribute to the harmful effects of UV-A radiation on the human skin. The fluorescence properties of the obtained tyrosine dimers have been established.